The dark side of disulfide-based dynamic combinatorial chemistry. Issue 31 (24th July 2020) - Dumartin, Mélissa; Septavaux, Jean; Donnier-Maréchal, Marion; Jeamet, Emeric; Dumont, Elise; Perret, Florent; Vial, Laurent; Leclaire, Julien
Abstract : We show that multiple analytical tools are necessary in order to describe the different phenomena within disulfide-based dynamic combinatorial libraries in terms of size, stereochemistry, affinity and selectivity. Abstract : During the last two decades, disulfide-based dynamic combinatorial chemistry has been extensively used in the field of molecular recognition to deliver artificial receptors for molecules of biological interest. Commonly, the nature of library members and their relative amounts are provided from HPLC-MS analysis of the libraries, allowing the identification of potential binders for a target (bio)molecule. By re-investigating dynamic combinatorial libraries generated from a simple 2, 5-dicarboxy-1, 4-dithiophenol building block in water, we herein demonstrated that multiple analytical tools were actually necessary in order to comprehensively describe the libraries in terms of size, stereochemistry, affinity, selectivity, and finally to get a true grasp on the different phenomena at work within dynamic combinatorial systems.